Aplicações médicas das abordagens complexas não lineares: a geometria fractal do EEG - Sant'Ana, Antonio Carlos [UNESP] (2015)
The use of nonlinear techniques (complex systems, fractal geometry and quantum physics), with approaches more related with the principles of chaos theory, is a growing tendency in the study of the natural sciences, and are being progressively presented as valid options to their correspondent measures in linear systems (simple structures, Euclidean geometry and newtonian classical physics), with their more Cartesian approaches. In this sense, neurobiology and acupuncture may help to shed some light upon this search. Aiming to evaluate the reach of the use of nonlinear techniques - more specifically the fractal dimension - a pilot experimental essay was taken in human beings in order to evaluate the sensibility of eletroencefalography in the identification of alterations resulting from the stimulation of auricular acupuncture points, according to clinical, neurophysiologic and fractal geometry criteria. Both male and female patients, having headache as a common but not exclusive complaint, were subject to eletroencefalographic examinations, before and after the stimulation of auricular acupuncture points, or after cycles of both auricular and systemic acupuncture follow up in an outpatient basis. The fractal dimensions calculated by the 'box counting method' were obtained with the aid of ImageJ software, using digitalized images from the eletroencefalographic examinations, and the results are presented as case reports. By analysing the variations in the fractal dimensions both by descriptive and quantitative approaches, observations were made on the evolutive behaviours either from the clinical or from the symptomatic condition of the patient, and their relationship with the concepts of chaotic development of the complex dynamic adaptative systems